Cardiovascular disease : diet, nutrition and emerging risk factors - Frayn, K. N. (Keith N.); Stanner, Sara; Coe, Sarah (London : Published by Blackwell Publishing for the British Nutrition Foundation, 2019)
c
Includes bibliographical references and index.
Keywords: Cardiovascular system -- Diseases -- Nutritional aspects; Cardiovascular system -- Diseases -- Risk factors